Hubungan Indeks Massa Tubuh dan Massa Lemak dengan Densitas Tulang pada Mahasiswa Fakultas Kedokteran Universitas Jendral Soedirman - Irbath Hamdanie; Agus Prastowo; Indah Rahmawati (JURNAL NUTRISIA, 2017)
Background : Osteoporosis is associated with decreased bone density. Osteoporosis needs serious handling because of the high prevalence and impact is quite severe. There are several factors that may affect bone density, there are body mass index and fat mass. Medical student are candidates for health professional who are required to have high criteria so that the health of medical students need to be considered. Objective : To determine the correlation between body mass index and fat mass with bone density in college student Medical Faculty of Jenderal Soedirman University. Methods : This was an analytic observational study with cross sectional approach. Total research subject were 36 college student. Body mass index data was obtained from rasio of weight in kg and quadrate from height in meter. Fat mass data was measured with Bioelectrical Impedance Analyzer (BIA). Bone density data was measured with densitometry. Bivariate analysis using pearson. Result : Value of body mass index in subject had a mean 24,91 ± 4,59. Value of fat mass in subject had a mean 21,95 ± 5,14%. Value of bone density in subject had a mean -0,28 ± 0,79. Pearson test’s result were p = 0,001 for body mass index (r=0,697) and p = 0,001 for fat mass (r=0,665), show there were statistically significant correlation (p<0,05) between body mass index and fat mass with bone density. Conclusion : There were significant correlation between body mass index and fat mass with bone density in college student Medical Faculty of Jenderal Soedirman University. Keywords : body mass index, fat mass, bone density, college student